Investigation of the financial stability of S&P 500 using realized volatility and stock returns distribution - Nahida Akter; Ashadun Nobi (Journal of Risk and Financial Management, 2018)
In this work, the financial data of 377 stocks of Standard & Poor's 500 Index (S&P 500) from the years 1998-2012 with a 250-day time window were investigated by measuring realized stock returns and realized volatility. We examined the normal distribution and frequency distribution for both daily stock returns and volatility. We also determined the beta-coefficient and correlation among the stocks for 15 years and found that, during the crisis period, the beta-coefficient between the market index and stock's prices and correlation among stock's prices increased remarkably and decreased during the non-crisis period. We compared the stock volatility and stock returns for specific time periods i.e., non-crisis, before crisis and during crisis year in detail and found that the distribution behaviors of stock return prices has a better long-term effect that allows predictions of near-future market behavior than realized volatility of stock returns. Our detailed statistical analysis provides a valuable guideline for both researchers and market participants because it provides a significantly clearer comparison of the strengths and weaknesses of the two methods.
Keywords: 330; volatility; stock return; correlation; beta-coefficient; financial stability